1957
DOI: 10.3181/00379727-95-23244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tolbutamide (Orinase) on Plasma Non-Esterified Fatty Acids

Abstract: driven isolated rabbit auricle. It is approximately 16 times as active as quinidine in antagonizing acetylcholine-induced auricular fibrillation in the dog. It is slightly more active than quinidine in antagonizing aconitine-induced tachycardia in the same species. The safety margin of this drug, as measured by the ratio between minimal anti-fibrillatory doses and those producing marked blood pressure and ECG changes, is greater than that of quinidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1958
1958
1968
1968

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The changes in the concentration of blood glucose and plasma FFA after intravenous tolbutamide are similar to those observed by Bierman et al 11 These responses differed considerably, however, from those we observed after the sulfonylureas were taken by mouth. After oral administration, neither the fall nor the rise in the FFA levels paralleled the change in the concentration of blood glucose.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The changes in the concentration of blood glucose and plasma FFA after intravenous tolbutamide are similar to those observed by Bierman et al 11 These responses differed considerably, however, from those we observed after the sulfonylureas were taken by mouth. After oral administration, neither the fall nor the rise in the FFA levels paralleled the change in the concentration of blood glucose.…”
Section: Discussionsupporting
confidence: 77%
“…These data confirm those of Bierman, Roberts and Dole. 11 One patient received intravenous acetohexamide. The data paralleled those with intravenous tolbutamide.…”
Section: Intravenous Sulfonylureamentioning
confidence: 99%